Fulfillment of Expectations After Orthopedic Foot and Ankle Surgery. (November 2019) - Henry, Jensen K.; Roney, Andrew; Cody, Elizabeth A.; Hummel, Amelia; Mancuso, Carol A.; Ellis, Scott
Background: To date, no study has assessed fulfillment of patients' expectations after foot and ankle surgery. This study aimed to validate a method of assessing expectation fulfillment in foot/ankle patients postoperatively. Methods: Preoperatively, patients completed the expectations survey, consisting of 23 questions for domains including pain, ambulation, daily function, exercise, and shoe wear. At 2 years postoperatively, patients answered how much improvement they received for each item cited preoperatively. A fulfillment proportion (FP) was calculated as the amount of improvement received versus the amount of improvement expected. The FP ranges from 0 (no expectations fulfilled), to between 0 and 1 (expectations partially fulfilled), to 1 (expectations met), to greater than 1 (expectations surpassed). Receiver operating characteristic (ROC) curves and areas under the curve (AUCs) with 95% confidence intervals (CIs) were used to compare the expectations survey to other outcome surveys, including Foot and Ankle Outcome Score, improvement, overall fulfillment, Delighted-Terrible scale, and satisfaction. Results: Of the 271 patients (mean age 55.4 years, mean BMI 27.5, 65% female), 34% had expectations surpassed (FP >1), 4% had expectations met, 58% had expectations partially fulfilled (FP between 0 and 1), and 5% had no expectations met. The mean FP was 0.84 ± 0.41 (range 0-3.13), indicating partially fulfilled expectations. FP correlated significantly with all outcome measures ( P ≤ .007). FP was associated most closely with satisfaction ( r = 0.66 [95% CI 0.57-0.75]; AUC = 0.92 [95% CI 0.88-0.96]; P < .001) and improvement ( r = 0.73 [95% CI 0.64-0.81]; AUC = 0.94 [95% CI 0.91-0.96]; P < .001). Based on the associations with satisfaction and improvement outcomes, a clinically important proportion of expectations fulfilled is 0.68, with sensitivity 0.85-0.90 and specificity 0.84-0.86. Conclusion: The proportion of expectations fulfilled is a novel patient-centered outcome that correlated with validated outcome measures. The expectations survey may be used by surgeons to counsel patients preoperatively and also to assess patients' results postoperatively. Level of Evidence: Level II, prospective comparative series.